Phenotypic and Genotypic Characterization and pollination tests of 18 Annatto (Bixa orellana L.) accessions in Costa Rica - Duque Y Duque, Enio Remberto (2022)
Introduction. Achiote (Bixa orellana L.) is a valuable species due to the bixin content present in the aril of its seeds; this pigment is used in the food, cosmetic and medicinal industries. Germplasm characterization is the starting point to initiate breeding programs and to identify the genetic variability of a germplasm bank. Objective. This project evaluated the phenotypic and genotypic differences of 18 achiote accessions from the EARTH University Germplasm Bank. Materials and methods. Phenotype was characterized by general and botanical descriptors detailing morphological and productive characteristics of the cultivars. Genotype was characterized based on analysis of the ITS2 region of ribosomal DNA to establish phylogenetic relationships among accessions and to determine relationships between phenotypic and molecular characteristics. Self-pollination trials were also carried out to evaluate the response of the accessions to this method leading to the obtention of pure lines. Results. The results from the Maximum Parsimony dendrogram allowed to differentiate five phylogenetic groups, which are closely related to the degree of spinosity of the capsules. By condensing the dendrogram to 50%, 2 groups were obtained, differentiated by the presence or absence of spines in the capsules, which positions this trait as a determinant for the grouping of materials. Accessions with spines had a higher number of seeds per capsule, while accessions without spines had a higher bixin content and higher seed weight. Selfpollination assays revealed apparent lateacting self-incompatibility in some accessions. Conclusion. This study generated information on the identification of the accessions and is a first phase aimed at obtaining homozygous lines to preserve the genetic identity of the accessions in the EARTH University Germplasm Bank.